Keragaman Genetik Bawang Putih Varietas Lumbu Kuning dan Lumbu Hijau Efek Iradiasi Sinar Gamma 60CO - Adin Novitasari; Afifuddin Latif Adiredjo; Lita Soetopo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Garlic has limited genetic variability because the offspring are phenotypically identical to the parent plant. One approach to increase variability is mutation breeding using gamma irradiation. This study aimed to evaluate the effects of different gamma-ray doses on growth characteristics, physiological traits, chromosome number, and to determine the LD₅₀ (lethal dose 50%) in Lumbu Kuning and Lumbu Hijau garlic varieties. The experiment was conducted from May to September 2021 in Ngroto Village, Pujon District, Malang Regency, using a single-plot design with observations on individual plants. Garlic bulbs were irradiated with gamma rays at doses of 0, 2, 4, 6, 8, and 10 Gy. The t-test analysis of the M0 generation indicated that gamma irradiation significantly affected growth parameters, including leaf length and width, number of leaves, and plant height, compared to the control. The lowest mean leaf length (7.81 cm), number of leaves (3.22), and plant height (12.32 cm) were observed in the Lumbu Hijau variety at 10 Gy, while the lowest leaf width (0.37 cm) occurred in Lumbu Kuning at 8 Gy, indicating phenotypic reduction at higher doses. The highest chlorophyll content (1,091 mg/g) was recorded in Lumbu Hijau treated with 8 Gy. Gamma irradiation also induced chromosomal abnormalities, including aneuploidy with chromosome numbers such as 2n=2x−1 and 2n=2x+4. These results demonstrate that low-dose gamma irradiation can generate useful variability for garlic improvement programs.